Violet Cane: A breaker of codes and moulds. Issue 5 (26th September 2022) - Gandy, Rob; Lorenzo‐Arribas, Altea; Startup, Richard
Abstract : She ditched her PhD to help defeat the Nazis, and is remembered as a kind teacher and funny friend. Here, Rob Gandy, Altea Lorenzo‐Arribas and Richard Startup celebrate the life and work of pioneering British statistician Professor Violet Cane Abstract : She ditched her PhD to help defeat the Nazis, and is remembered as a kind teacher and funny friend. Here, Rob Gandy, Altea Lorenzo‐Arribas and Richard Startup celebrate the life and work of pioneering British statistician Professor Violet Cane